"Loss of a limb is not loss of a life". Knowledge and attitude on diabetic foot ulcer care and associated factors among diabetic mellitus patients on chronic care follow-up of southwestern Ethiopian hospitals: A multicenter cross-sectional study. (December 2021) - Bekele, Firomsa; Berhanu, Daniel
Abstract: Background: Diabetic foot ulcer (DFU) is a full-thickness wound penetrating through the dermis located below the ankle in a diabetes patient. The incidence of diabetic foot ulcers has increased due to the worldwide prevalence of diabetic mellitus (DM) and the poor knowledge and attitude of diabetic foot self-care. Therefore, the study was aimed to assess the knowledge and attitude on diabetic foot ulcers and associated factors among diabetic mellitus patients of southwestern Ethiopian hospitals. Methods: A multicenter cross-sectional study design was used. All diabetic patients fulfilling the inclusion criteria and treated as outpatient in the study period from August 9, 2021 to September 5, 2021 G was interviewed through a semi-structured questionnaire at Bedele General Hospital and Mettu Karl Comprehensive Specialized Hospital. Data was analyzed using a statistical package for social science (SPSS 23 version). Result: Out of 387 diabetic patients, 234(60.5) were male and 266(68.7%) were married. The mean age of the participants was 41.73(SD ± 15.637) years and the majority 87(22.5) of the patients age were greater than 55 years. A total of 11(28.7%) patients had a diabetes mellitus duration between 5 and 10 years and more than half 213(55%) of the patients had a co-morbidity. Regarding the diabetic foot care, a total of 180(46.5%) and 257(66.4%) of the patients had good knowledge and attitude, respectively. Educational level(AOR = 2.705(1.380-5.299), P = 0.004) and age[AOR = 1.254(0.768–2.048), P = 0.017] were the predictors of knowledge. Monthly income (AOR = 2.879(1.043–7.944), P = 0.041), educational level (AOR = 2.415(1.121–5.20), P = 0.024), previous information (AOR = 4.022(2.311–7.000), P < 0.001) and previous history of foot ulcers (AOR = 1.976(1.126–3.466), P = 0.018) were factors associated with the attitude of diabetic foot ulcer. Conclusion: More than half of the study participants had poor knowledge while the majority of them had a good attitude. Educational level and age were significantly associated with knowledge. Monthly income, educational level, previous information, and previous history of foot ulcers were predictors of attitude towards diabetic foot care. Therefore, the health care providers should provide diabetic foot care education to reduce further complications of foot ulcers. Besides this, special attention should be given to patients who developed diabetic foot ulcers and have low socio-economic status. Highlights: Diabetes mellitus (DM) is a diverse group of metabolic disorders that is resulted from increased blood glucose level. Diabetic foot ulcer (DFU) is a full-thickness wound penetrating through the dermis in a diabetes patient. Proper patients' awareness about foot care is important defense line in preventing DF problems and amputation.